Analysis of Bored Pile Foundation Bearing Capacity Based on Cone Penetration Test Data (Case Study: Cilellang Weir Location) - Mutiara, Indra (INTEK: Jurnal Penelitian, 2021)
The use of a bored pile foundation is an alternative in planning deep foundations. The function of this bored pile foundation is more or less the same as other deep foundations such as piles but has a slight difference in the process. The bored pile foundation begins with drilling the ground to the planned depth, followed by the installation of steel reinforcement and then concrete mortar. This study aims to evaluate the Cone Penetration Test (CPT) data on the bearing capacity of the bored pile foundation. Calculation of bearing capacity from Cone Penetration Test (CPT) data using the Schmertmann & Nottingham method and the Mayerhof method. Based on CPT data, the percentage calculation of ultimate bearing capacity at location S1 with the Schmertmann & Nottingham method is more optimistic Â±17.28% compared to using the Mayerhof method for bored pile diameters of 60 and 80 cm, while for bored pile diameters of 40 cm, calculations using the Mayerhof method show more optimistic by 21.89%. The percentage calculation of ultimate bearing capacity at location S2 using the Schmertmann & Nottingham method is Â±11.66% more optimistic than using the Mayerhof method for bored pile diameters of 60 and 80 cm, while the diameter of the bored pile 40 cm, the calculation using the Mayerhof method shows a more optimistic result of 33.82%.